If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+3=(x-2)/3
We move all terms to the left:
3(2x+3-((x-2)/3)=0
We multiply all the terms by the denominator
3(2x+3-((x-2)=0
| 6q^2-4q=5q^2-7q+28 | | 3d-2=5-(2d-3) | | 3/5=6/x+4 | | 18/14=27/x | | 6-3y=14 | | -3(5a-8)=20 | | -7(1+x)=63 | | 6×(3x-7)-12-4x=9x-(7x+6) | | 6(1x+2)=36 | | (5x+1)+(x+17)=180 | | 3(6x+2)=6 | | (X+17)=(5x+1) | | -129=8(c-6)+7 | | 5y-9y=25 | | 2x-3(2x+1)=4 | | (3x+1)=121 | | 7(-7x+9)=-378 | | 2/15m+1/5=4/5 | | 12+3x=2(x+1) | | (X+29)+(4x+1)=180 | | -6(6+6x)=-468 | | 3x=22+5x | | (3x)+(x+10)=90 | | 5(-6x+10)=80 | | 3/5x-2=26 | | (3x)=(x+10) | | -7x-10=-94+7x | | 12m-7=65 | | (6x-7)=(5.5x-3) | | 5n+30=180 | | 12+3x=(x+1) | | n/3+11=4.7 |